Effects of Smoking, Drinking, and Urban Environment on Obesity in Seoul, Korea - Haejung CHUN (Tehran University of Medical Sciences, 2020)
Background: The level of obesity is related to spatial characteristics around the individual. The objective of this study was to empirically analyze the effect of smoking, drinking, and urban environment on obesity in community residents. Methods: This study was conducted for empirical analysis using Ordinary Least Squares (OLS) model not considering time or space-effects, Temporal Autoregressive (TAR) model considering time-effect only, Spatial Autoregressive (SAR) model considering space-model only, and STAR model considering both time and space effects. This study covered 25 autonomous districts in Seoul City, South Korea in terms of space and from 2009 to 2014 in terms of time. Results: The STAR model yielded an adjusted R square higher than that from OLS, TAR, or SAR model. Empirical results from the STAR model showed significantly positive (+) effects of the ratio of dependent elders, ratio of smokers, ratio of drinkers, and areas of retail floor space on obesity. In contrast, effects of length of bicycle road and the amount of collected local tax on obesity were negative (-) with statistical significance. Conclusion: Smoking and drinking rate and the length of bicycle road can contribute to personal obesity.